Comparative study of different approaches of myringoplasty in chronic otitis media (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To determine the best surgical approach of myringoplasty regarding healing of tympanic membrane and improvement of hearing.Methods: This was a cross sectional comparative study carried out in the departments of Otolaryngology and Head-Neck Surgery of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital, Sir Salimullah Medical college Mitford Hospital and Shaheed Suhrawardy Medical College Hospital during the period of July’2009 to March 2011. A total number of 75 patients of age 15-45years having inactive mucosal chronic otitis media with central perforation were included in this study. All patients has undergone myringoplasty and patients were divided into three groups according to surgical approach such as postaural, transcanal and endaural. All patients were followed up postoperatively and all postoperative findings were recorded. The three groups were compared with regard to healing of tympanic membrane and improvement of hearing.Results: The success rate in this study was 80% . graft take rate in postaural, transcanal and endaural approaches were 92.5%, 66.67% and 63.64% respectively. Improvement of mean airbone gap in postaural, transcanal and endaural approaches were 19.04dB, 10.02dB and 11.36dBConclusion: Graft take rate and hearing improvement is significantly higher in postaural approach than other approaches.Bangladesh J Otorhinolaryngol; April 2016; 22(1): 21-25